Fungsi Satuan Polisi Pamong Praja Provinsi Bali dalam Memelihara Ketentraman dan Ketertiban Masyarakat - Putu Gede Indra Paramartha; I Wayan Arthanaya; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2020)
The Civil Service Police Unit in the Province of Bali is indispensable and can be said to be one of the law enforcement officers. The formulation of the problems used in this study are: (1) How is the Function of the Bali Civil Service Police Unit in maintaining peace and public order; (2) How is the strategy of the Bali Province Satpol PP Work Unit in overcoming obstacles in conducting supervision and control. This research was conducted using normative legal research. As for the source and type of material of this research are primary legal materials which are looking at the laws and secondary legal materials written the experts and the results of the scientists are then processed and analyzed descriptively to get a conclusion. Based on the results of the research it can be concluded that the Bali Civil Service Police Unit (Satpol PP) has the function of maintaining and maintaining security and order and also helps the regional head to create a policy regional peace, orderly, and orderly so that the administration of government can run smoothly and the community can carry out its activities safely. The strategy to overcome obstacles in conducting oversight and control is expected to be that SATPOL PP always coordinates with related parties / agencies